Kemampuan Komunikasi Siswa Ditinjau dari Persepsi Siswa tentang Layanan Bimbingan Kelompok dan Keharmonisan Keluarga - Siti Taradita Wahyuningtiyas; Ninik Setyowani; Heru Mugiarso (Psychocentrum Review, 2019)
This research designed to exploring interpersonal communication based on students perceptions of group guidance and the harmony of their family. This is correlational research using an ex post facto design. We managed a survey of 155 junior high school students. The results presented that (1) there was a significant influence between students perceptions of group guidance services and students interpersonal communication skills; (2) there was a significant influence between family harmony and interpersonal communication skills, and; (3) there was a significant influence about group guidance services and family harmony with students interpersonal communication skills. The findings on this study provide us information that students perceptions of group guidance and family harmony contribute to the influence of students interpersonal communication skills. If students have a good perception of group guidance services and family harmony, then the interpersonal communication skills possessed by students are also getting better.